EFFECT OF RETURN ON ASSET, DEBT TO ASSET RATIO, QUICK RATIO AND TOTAL ASSET TURN OVER ON STOCK PRICE IN THE CHEMICAL SECTOR COMPANY LISTED ON INDONESIA STOCK EXCHANGE - Farisa Luvita Simatupang; Ade Gunawan (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to: (1) To analyze and determine the effect of the Variable Return on Assets on Stock Prices in Chemical companies on the Indonesia Stock Exchange. (2) To analyze and determine the effect of the Debt to Assets Ratio variable on the Share Price of Kimia companies on the Indonesia Stock Exchange. (3) To analyze and find out the effect of the Quick ratio on the Price of Shares in Chemical companies on the Indonesia Stock Exchange. (4) To analyze and determine the effect of Total Assets Turn Over on Stock Price on Chemical Performance on the Indonesia Stock Exchange. (5) To analyze and determine the effect of Return On Assets, Debt To Assets Ratio, Quick Ratio and Total assets Turn Over on the share price of Chemical companies on the Indonesia Stock Exchange. The population usedn in this study is a chemical subsector listed on the Indonesia Stock Exchange from 2015 to 2020 totaling 12 companies. The data collection technique in this study used documentation techniques. The data analysis technique in this study uses classical assumption test, multiple linear regression, t test and F test, and coefficient of determination. Data management in this study used the SPSS 23 Software program. Based on the results of the study, it shows that the Return on Assets has a significant positive effect on the Share Price of Chemical companies listed on the Indonesia Stock Exchange for the 2015-2020 period. Debt To Assets Ratio has an insignificant positive effect on the Share Price of Chemical companies listed on the Indon esia Stock Exchange forthe 2015-2020 period. The Quick Ratio has an insignificant positive effect on the Share Price of Chemical companies listed on the Indonesia Stock Exchange for the 2015-2020 period. Total Assets Turn Over has an insignificant positive effect on the Share Price of a Chemical company listed on the Indonesia Stock Exchange for the 2015-2020 period. Return On Assets, Debt To Assetss Ratio, Quick Ratio and Total Assets Turn Over together have a positive and significant effect on the Share Price of chemical companies listed on the Indonesia Stock Exchange for the 2015-2020 period.